Aging and corrosion behavior of epoxy primer coated aluminum alloys in UVA, UVA-neutral and UVA-acidic alternating-immersion environments. (December 2021) - Zhang, Tianyu; Zhang, Teng; He, Yuting; Du, Xu; Zhang, Sheng
Graphical abstract: Highlights: After the UVA + AI test, the remaining thickness degrades linearly with time. Immersion could affect the chemical corrosion degradation of the epoxy coatings. The corrosion mechanism can be characterized by equivalent circuit models. Impedance is affected by several effects. Abstract: Epoxy primer coated aluminum alloys are artificially aged in three environments: UVA, UVA-neutral and UVA-acidic alternating-immersion. The corrosion morphology, corrosion products, electrochemical impedance, and molecular structure of the coated specimens are explored using SEM, EDS, EIS, and ATR-FTIR. The results demonstrate that the residual thicknesses of the primer decrease linearly under UVA-acidic alternating-immersion. The impedances of the coated specimens change in different ways in the three environments, which are influenced by the synergistic effect of the accumulation and dissolution of corrosion products, and post-curing of the primer. The degradation mechanisms and electrochemical equivalent circuits are analyzed at different stages.